2002
DOI: 10.4315/0362-028x-65.11.1796
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Listeria monocytogenes Isolated from Various Cabbage Farms and Packing Sheds in Texas

Abstract: Twenty-one isolates of Listeria monocytogenes from cabbage, environmental, and water samples were evaluated for antimicrobial resistance by the disk diffusion method. Ninety-five percent (20 of 21) of the isolates tested were resistant to two or more antimicrobial agents. This finding is significant, since multiresistant strains of Listeria spp. are not commonly found in nature. Eighty-five percent (17 of 20) of the multiresistant strains were resistant to penicillin, and the remaining multiresistant isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 22 publications
3
14
0
2
Order By: Relevance
“…Although it was previously considered that multiresistant strains of Listeria spp. are not commonly found in nature, evidence of the emergence of multiresistant L. monocytogenes strains from various sources has been reported (15,16,18). Our results provide further evidence of the emergence of multiresistant strains in nature, representing a potential threat to human health.…”
supporting
confidence: 56%
“…Although it was previously considered that multiresistant strains of Listeria spp. are not commonly found in nature, evidence of the emergence of multiresistant L. monocytogenes strains from various sources has been reported (15,16,18). Our results provide further evidence of the emergence of multiresistant strains in nature, representing a potential threat to human health.…”
supporting
confidence: 56%
“…In addition, strains resistant to penicillin (50%) were observed. Prazak and Murano in their study reported the isolation of bacteria susceptible to all antibiotics except penicillin, which corresponds to the results of our study (23). Arslan and Ozdemir (20) in their study reported resistance to penicillin and chloramphenicol, which are in agreement with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Prazak et al 15 encontraram resultados muito parecidos, onde 95% das cepas de L. monocytogenes oriundas de amostras de repolho, do meio ambiente e de água foram resistentes a dois ou mais antimicrobianos, e 85% destas demonstraram resistência à penicilina. Antunes et al 12 também isolaram cepas de L. monocytogenes, a partir de carcaças de frango, com múltipla resistência antimicrobiana em 74% das amostras analisadas.…”
Section: Resultsunclassified